2020
DOI: 10.1111/dsji.12203
|View full text |Cite
|
Sign up to set email alerts
|

Gamification of Entrepreneurship Education

Abstract: Gamification—the use of gameplay mechanics for nongame applications—enables learning by doing, yet questions abound about its effectiveness for education. This teaching brief reports on the gamification of an entrepreneurship course using a stand‐alone gamification platform integrated with Shopify, a global e‐commerce platform for online stores. Students experienced the entire entrepreneurship process from ideation to launch of a real business and beyond. A live leaderboard allows tracking of team performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 41 publications
2
55
0
6
Order By: Relevance
“…Moreover, participating in gaming has enhanced the students' critical thinking which is also supported by scholars who evaluated the learning modules based on interactive gaming and learning materials (e.g. Huang and Yeh 2017;Isabelle 2020;Rosli et al 2019).…”
Section: Negotiation Process and Critical Thinkingmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, participating in gaming has enhanced the students' critical thinking which is also supported by scholars who evaluated the learning modules based on interactive gaming and learning materials (e.g. Huang and Yeh 2017;Isabelle 2020;Rosli et al 2019).…”
Section: Negotiation Process and Critical Thinkingmentioning
confidence: 89%
“…Torres-Toukoumidis et al ( 2019 ) noted the importance of preparing a learning platform with gamification in the context of selecting for entrepreneurial competences. Isabelle ( 2020 ) further discussed the impact of gamification from an entrepreneurial education perspective, while also noting that supportive decision-making should also be analysed and evaluated. This discussion reveals that it would be good practice to launch an online gamification learning measure, as this is likely to have a supportive technological impact on entrepreneurial education and enable the development of actionable implications for pedagogical stakeholders and researchers.…”
Section: Interactive Learning Based On a Virtual Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…If students are not participatory and an educative environment does not arise naturally, it is necessary to create more interesting learning modules. Many researchers have already investigated various forms of education that have used games (Bai et al, 2020;Isabelle, 2020;Ofosu-Ampong, 2020).…”
Section: Figure 2 a Virtual Learning Platform With Mmo In The Classroommentioning
confidence: 99%
“…The approach is thought to resonate with millennial students (Poole et al, 2014) and, more recently, has been shown to increase student engagement (e.g., Dias, 2017). It has been used to teach concepts in data systems (Yang & Guo, 2020), learning curves (Robbins, 2019), entrepreneurship (Isabelle, 2020), transportation (Rossetti, 2018), customer experience quality (Paul & Ponnam, 2018), and externalities (Giraud-Carrier & Schmidt, 2015), among others. What are game elements?…”
Section: Game Elements In Pblmentioning
confidence: 99%